Soil-roots composite: correlation between shear strength and some plant properties - Ali, F.H.; Osman, Normaniza (2007)
The roots and rhizomes of the vegetation interact with the soil to produce a composite material in which the, roots are fibres of relatively high tensile strength and adhesion embedded in a matrix of lower tensile strength. The shear strength of the soil may therefore be enhanced by the root matrix. This paper describes an investigation on the reinforcing effect of soil-root matrix in the laboratory using a modified large shear box apparatus (300 mm × 300 mm). Four different species of plant namely Vertiveria zizanoides, Leucaena leucocephala, Bixa orellana and Bauhinia purpurea were planted in special boxes containing residual soil compacted to a known density. The results shows that roots significantly contribute to the increase in soil shear strength. The presence of the roots only affects the apparent cohesion of the soil and no significant change in angle of friction is observed. L. leucocephala shows the outstanding increase in its root strength in which the strength varies with depth and time e.g. under soil suction-free condition (matrix suction = 0). The roots have increased the cohesion by 116.6% (0.1m), 225.0% (0.3m) and 413.4% (0.5m) after six months of growth. In twelve months, it is observed that the increase in cohesion is more than three-fold of the six months growth period at 0.1m depth. The results also indicate that shear strength is influenced by root profile and to some extent, the physiological parameters of the plants.